Evaluation of nutritional components by Plackett-Burman design for Penicillium citrinum lipase production using palm oil mill effluent - Salihu, Aliyu; Alam, Md. Zahangir; Abdulkarim, Mohd Ismail; Hamzah, Mohd. Salleh (Academic Journals, 2011)
A number of medium components influencing lipase production by Penicillium citrinum (ATCC 42799) were studied using palm oil mill effluent (POME) as the basal medium. The medium components (peptone, yeast extract, malt extract, NH4Cl, NaNO3, KH2PO4, CaCl2, MgSO4, olive oil and Tween-80) were analyzed in twelve experimental trials using Plackett–Burman (PB) design. The most significant components affecting lipase production were found to be Tween-80, peptone, yeast extract, malt extract and NaNO3 at p < 0.05. The results indicate the efficiency of using PB design for screening processes. However, optimal concentration of the significant components can be determined by further statistical analysis.